Prevalence of extended high-frequency hearing loss among adolescents from two rural areas in Colombia (2020)
Objective: Worldwide research trends on the prevalence of hearing loss within young rural populations are scarce. Current evidence suggests extended high-frequency audiometry could be a sensitive predictor to detect subclinical hearing loss. This study aimed to determine the prevalence of hearing loss through conventional pure tone (0.25–8 kHz) and extended high-frequency (9–20 kHz) audiometry tests in a group of adolescents aged 13 to 19 years old from two rural areas of Colombia. A sociodemographic and associated factor for hearing loss questionnaire was applied. Design: Cross-sectional study. Study Sample: Three hundred sixty-six adolescents aged 13 to 19 years old from two rural municipalities in Colombia: Soracá, and Palmas del Socorro. Results: Hearing loss prevalence assessed through pure tone audiometry was 3.28% in right ears and 3.83% in left ears while through extended high-frequency audiometry was 14.21% and 13.11%, respectively. Associated factors found by the logistic regression were age (OR: 1.36; CI 95% 1.13-1.64) and obesity (OR: 3.74; CI 95% 1.07-13.11). Conclusions: Using 15 dB as the normal hearing threshold parameter for audiometric frequencies, our results suggest that extended high-frequency hearing loss is already widespread among rural adolescents. This highlights the need for research on extended high-frequency audiometry in rural school-aged children.